Pengaruh Tawakal terhadap Pencarian Rezeki sebagai Guru - Muhammad Syahrul Munir (MODELING: Jurnal Program Studi PGMI, 2018)
Profession of teacher do not make as a basical subject of livelihood. But must be consciously that teach as a obligation to channel of knowledge. Because of that, this papper research have a tawakal implanted in a teacher attitude? Which their attitude dominated by sincerity. This research used method of qualitative research with psychology approach. This research found that tawakal still dominate of teacher attitude, although sometime there are feeling unsincerity and unsatisfaction with their wage.